PENGARUH KEPRIBADIAN DAN IKLIM ORGANISASI TERHADAP KEPUASAN KERJA DENGAN MEDIASI KOMITMEN ORGANISASIONAL (Studi pada Kantor Kecamatan dan Kelurahan di Kota Tegal ) - Mohamad Afin, 11 52.02 0075 (Students Journal of Economic and Management, 2013)
The study was conducted onÂ employees at the District Office and Village Tegal in order to test and analyze whether influence of personality and organizational climate on Job Satisfaction with organizational commitment as mediation. Sampling method with purposive sampling . Data is were collected by questionnaires and tests conducted by the research instrument validity and reliability testing, while the statistical test used was multiple regression analysis . The research results showed that personality had no effect on organizational commitment and job satisfaction. Organizational Climate has positive effect on organizational commitment and job satisfaction Organizational commitment as a mediating variable based on the study was not able to explain the indirect effects of personality and organizational climate on job satisfaction in the Office of the District and Sub-District in the city of Tegal. Keywords: Personality, organizational climate, organizational commitment, Â Â and job satisfactio